Preparation of Nano-composite Gel Electrolytes with Metal Oxide Additives for Dye-sensitized Solar Cells. (10th September 2016) - Chang, Wei-Chen; Sie, Sian-Yang; Yu, Wan-Chin; Lin, Lu-Yin; Yu, Ying-Jung
Graphical abstract: Highlights: SiO2, TiO2, and ZnO nanoparticles are used to solidify the liquid electrolyte. The electrolyte was used for quasi-solid-state dye-sensitized solar cells (DSSCs). The concentrations of I2, LiI and nanoparticles in the electrolyte are optimized. The DSSC with ZnO nanoparticle gelators shows the highest efficiency ( η ) of 4.17%. The optimized DSSC shows a stability of 95% on the η value for 150 days. Abstract: The dye-sensitized solar cell (DSSC) has been widely studied due to the low-cost and interesting efficiencies. The solar-to-electricity conversion efficiency ( η ) is an important factor governing the performance of DSSC, so is the long-term stability. In this study, three kinds of inorganic nanoparticles, i.e., SiO2, TiO2, and ZnO, are employed to solidify an acetonitrile-based liquid electrolyte for quasi-solid-state DSSCs based on ZnO photoanodes. The concentrations of I2 and LiI in the liquid electrolyte are first optimized with respect to the diffusion-limited current density of I3 − ions and the photovoltaic performance of DSSC. Different amounts of the inorganic nanoparticles are then introduced into the optimized liquid electrolyte to accomplish gelation for quasi-solid-state DSSCs. All the nanoparticles tested can accomplish gelation while achieving a η higher than the reference liquid-state cell. The highest η of 4.17% was recorded for quasi-solid-state DSSCs under simulated full sunlight (AM1.5G, 100 mW/cm 2 ) with 35.0 wt% ZnO nanoparticles as the gelator. This is due to an enhancement in short-circuit current density and open-circuit voltage as a result of efficient charge transfer channels and improved electron lifetime generated by the gelling nanoparticles. The electrochemical impedance spectroscopy was also applied to analyze the interfacial resistances in the devices. The optimized quasi-solid-state DSSC also shows excellent at-rest stability exhibiting 95% retention of the η value after 150 days of storage.